Information needs and information-seeking behavior of doctors at the University of the Philippines College of Medicine-Philippine General Hospital (UPCM-PGH) a user study - Tinay, Froilan P.; Quiros, Edgardo B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2003)
The explosion of medical knowledge has been so overwhelming that doctors today are experiencing an information overload. This situation gets worse day by day and will continue to do so in the foreseeable future. To cope with this problem, it is vital to study the information needs and patterns of information and library use of doctors. It is essential to the design of information systems in general and to the provision of effective information services in particular.
This study seeks to determine the information needs and information-seeking behavior of doctors at the University of the Philippines College of Medicine-Philippine General Hospital (UPCM-PGH). Specifically, it aims to determine the following: (1) major information sources and services used; (2) quality of available information; (3) constraints relating to access to information; (4) user satisfaction; (5) patterns of information seeking; (6) extent to which computer-based information services are used; and (8) future demands for various types of services. It was conducted in cooperation with the UP Medical Informatics Unit (MIU). The study employed the descriptive survey method and the main data gathering tool used was a questionnaire. It was divided into five parts: questions on information needs, questions on information seeking, questions on information sources and services, questions on other sources of information, and questions on information systems ideas. There were one hundred forty-three respondents that consist of residents, consultants, and clinical faculty. Analytical techniques adopted include tabular and graphical presentations of data and use of percentages. The following conclusions were reached: 1. Most of the respondents need information and information systems for research and patient care; 2. Internet browsing and attending conferences and scientific meetings are the most popular form of information-seeking activities; 3. The main barrier to obtaining needed information is the lack of time due to the busy and often erratic schedules of doctors; 4. And also due to this, most of the respondents use the library rarely; 5. The library was rated as satisfactory; 6.The most important information source are journals;7. Hence, they clamored for more journal subscriptions that are complete and sustained.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines Manila. Physicians -- Philippines -- Manila; Library use studies -- Philippines